Information Technologies and Globalization - Dilnawaz A. Siddiqui (International Institute of Islamic Thought, 1998)
Technology is defined as a device to compensate for human physical, psychological, and mental limitations. It is usually neutral, but can have functional and dysfunctional aspects based on its users’ intentions. Historically, the technological haves have justified the existence and possession of new technologies, have publicized their own innocence and sense of responsibility in using them, and have asserted the innocuousness of their devices without necessarily sharing all of their secrets. Concerned and helpless, the technological have-nots have resisted them and, having suffered their deadly devastation, have tried to obtain them at great risk to themselves. However, the situation of information technology/-ies (IT) is different and more interesting. The haves have attempted to popularize their use globally for commercial and other reasons. Many have-nots are embracing them wholeheartedly, while some are more cautious. One motivation behind the use of these technologies is globalization. The increasingly popularized term globalization is rather vague and complex, allowing a variety of interpretations and hidden intentions. The have-nots seem to see it as the West’s redoubled efforts at Westernizing the world with all its pains, pleasures, and perversions; as achieving political hegemony as the sole superpower after the end of the Cold War; and as the “opening up of the globe” for commercial control on its own terms. Initially the world, especially the nations of South Asia, saw for themselves a rare opportunity in the globalization of trade and IT. But since the contagion has now spread, rather too fast, across the globe, the world can see more clearly both the prospects and the problems of these two major global trends. The purpose of this paper is to identify various issues involved in these trends, and to discuss, in greater depth, some of them, namely, global business, the promise of technology, and the globalization of media and culture ...